Ibrutinib and rituximab plus cyclophosphamide, doxorubicin, vincristine and prednisone in patients with previously untreated non‐germinal centre B‐cell‐like diffuse large B‐cell lymphoma: A Chinese subgroup analysis of the phase III PHOENIX trial - Jun Zhu; Xiaonan Hong; Yu Qin Song; Brendan Hodkinson; Sriram Balasubramanian; Songbai Wang; Qingyuan Zhang; Yuankai Shi; Huiqiang Huang; Huilai Zhang; Yan Zhu; Stephen Martin Shreeve; et al. (eJHaem, 2022)
Abstract In this post hoc subgroup analysis of 200 patients enrolled in China from the phase III PHOENIX trial (N = 838, NCT01855750), addition of ibrutinib to rituximab plus cyclophosphamide, doxorubicin, vincristine and prednisone (R‐CHOP) did not improve event‐free survival (EFS) versus placebo+R‐CHOP in the intent‐to‐treat (ITT; n = 200, hazard ratio [HR] = 0.83, 95% confidence interval [CI]: 0·509–1.349; p = 0.4495) or activated B‐cell‐like (ABC; n = 141 [based on available gene‐expression profiling data], HR = 0.86, 95% CI: 0.467–1.570; p = 0.6160) subpopulations. However, ibrutinib+R‐CHOP improved EFS (HR = 0·50, 95% CI: 0.251–1.003) and progression‐free survival (PFS; HR = 0.48, 95% CI: 0.228–1.009) versus placebo+R‐CHOP in patients aged <60 but not ≥60 years. Grade ≥3 serious treatment‐emergent adverse events occurred more with ibrutinib+R‐CHOP (45·6% vs. 31·3%). The percentage of patients receiving ≥6 cycles of R‐CHOP was similar across treatment arms in those <60 years. A numerical trend was seen towards improved EFS and PFS with ibrutinib+R‐CHOP versus placebo+R‐CHOP in patients with MYC‐high/BCL2‐high co‐expression. In this slightly younger Chinese subgroup, ibrutinib+R‐CHOP did not improve EFS in the ITT and ABC subpopulations but improved outcomes with manageable safety in patients <60 years, consistent with overall PHOENIX study outcomes.